POSSIBILITIES TO IMPROVE THE FUNCTIONING OF HIGH CAPACITY BELT CONVEYERS TMC 1800 FROM JILȚ SUD QUARRY - Răzvan Bogdan ITU (Fiabilitate şi Durabilitate)
The totality of the machines which ensure the excavation, transportation and depositing of the minig masses make up a flow sheet. High capacity belt conveyers are transport equipments in continuous flux with very high transportation capacities. They are designed to function within a continuous transportation flux from coal minig plants. One condition on which depends the good functioning and obtaining a transportation cost as reduced as possible is the correct choosing of the type and main parameters of the transporter, depending on the concrete minig conditions. In this work, we show a study concerning the enhacning of the funtioning of high capacity conveyer belts.